2010
DOI: 10.1007/s12072-010-9203-5
|View full text |Cite|
|
Sign up to set email alerts
|

Occult hepatitis B in blood donors in Indonesia: altered antigenicity of the hepatitis B virus surface protein

Abstract: Background and aims Occult hepatitis B virus infection (OBI) poses a challenge to the safety of blood donation. The prevalence of OBI is not well documented in Indonesia, although this information in such an endemic country is needed. This study was aimed to evaluate the prevalence of occult hepatitis B in blood donors from two cities of Indonesia, and to study the genetic variation and its effect on the predicted antigenicity of HBsAg. Methods Serum samples of 309 regular blood donors negative for HBsAg were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 34 publications
0
23
2
1
Order By: Relevance
“…In endemic countries, more than 10-15% of individuals had isolated HbcAb positivity and blood of these persons may be put down. [9] The minimum age for blood donation was 30 years in here, so we recommended that younger persons are also encouraged to donate blood. [10] Military persons have at least participated for blood donation attention to health man present in this group need also encourage for blood donation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In endemic countries, more than 10-15% of individuals had isolated HbcAb positivity and blood of these persons may be put down. [9] The minimum age for blood donation was 30 years in here, so we recommended that younger persons are also encouraged to donate blood. [10] Military persons have at least participated for blood donation attention to health man present in this group need also encourage for blood donation.…”
Section: Discussionmentioning
confidence: 97%
“…[15] HbcAb was positive in 20.2% of cases and its positive had significant upper HbsAb titer than HbcAb-negative persons (P < 0.000) that may be due to ancient hepatitis B infection and then cured but it should be considered that HbcAb positive may had occult hepatitis and may be transmitted to blood-recipient patients; therefore, we counsel not to use their blood, especially for immunodeficiency patients such as transplant. [9] Therefore, for better safety of blood, we consider anti-HBc as shown to be a better screening parameter than HBsAg [16,17] The prevalence of HbcAb positivity in our country is very high than European countries that may be owing to intermediate prevalence of hepatitis B infection and there is high risk of transmission of HBV through blood donation ,and it caused deferral blood increase, in the way we considered HbcAb should be screened before blood donation. [8,18] In here, at least 3 times blood donation was seen in 10.4% and 11 time in 0.2%.…”
Section: Discussionmentioning
confidence: 99%
“…49 The M133L mutation that was identified in this study, sample KM 61, was also previously reported in occult HBV infection among adult blood donors and vaccinated children in Indonesia. 50,51 This mutation showed the least significant changes in antigenicity profile (compared with T143M/L, T123N, and M133IT/V), which may have slightly decreased the sensitivity of the HBsAg assay. 52,53 Other mutation types in samples PB 53 and SS 112, that is, S155F and P120S-A159V, respectively, should be studied further in the future to determine their association with vaccination failure.…”
Section: Discussionmentioning
confidence: 99%
“…Nested polymerase chain reaction (PCR) using two sets of primers (S2-1/S1-2 [5′-CAA GGT ATG TTG CCC GTT TG-3′/5′-CGA ACC ACT GAA CAA ATG GC-3′] and S088/S2-2 [5′-TGT TGC CCG TTT GTC CTC TA-3′/5′-GGC ACT AGT AAA CTG AGC CA-3′]) was performed targeting an S gene segment encoding the "a" determinant of HBsAg. [30][31][32][33][34] Denaturation, annealing, and extension were done at 94°C for 30 seconds, 55°C for 30 seconds, and 72°C for 90 seconds/1 minute for the first/second PCR rounds (35/ 30 cycles), respectively. This nested PCR method was capable of detecting HBV DNA at very low titer (< 6 IU/mL), as validated using a panel of sera with known HBV DNA titers based on quantitative real-time PCR (Cobas TaqMan™ HBV Test; Roche Diagnostics, Indianapolis, IN) (Supplemental Table 1).…”
Section: Methodsmentioning
confidence: 99%